Surface plasmon field-enhanced fluorescence spectroscopy in PCR product analysis by peptide nucleic acid probes - Yao, Danfeng (Oxford University Press, 2004)
Surface plasmon field-enhanced fluorescence spectroscopy (SPFS) was recently developed for PCR product analysis, which allowed for real-time monitoring of hybridization processes and for the detection of trace amounts of PCR products, with a detection limit of 100 fmol on the peptide nucleic acid (PNA) probe surface, and 500 fmol on the DNA probe surface. By selectively labeling the strands of PCR-amplified DNA, it was shown that the heat denaturation process in combination with the application of low-salt condition substantially reduced the interference from the antisense strands and thus simplified the surface hybridization. Furthermore, SPFS was demonstrated to be capable of quantitatively discriminating the difference induced by single nucleotide substitution, even within one minute of contact time.